2023
DOI: 10.1001/jamaoncol.2023.0444
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Decolonization for Prevention of Radiation Dermatitis

Abstract: ImportanceEvidence-based approaches for the prevention of acute radiation dermatitis (ARD) are limited, and additional strategies are necessary to optimize care.ObjectiveTo determine the efficacy of bacterial decolonization (BD) to reduce ARD severity compared with standard of care.Design, Setting, and ParticipantsThis phase 2/3 randomized clinical trial was conducted from June 2019 to August 2021 with investigator blinding at an urban academic cancer center and enrolled patients with breast cancer or head and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The Fragility Index (FI) is an epidemiological tool that can quantitatively assess this counterfactual and determine the minimum needed change in number of events for the results to become nonsignificant . We calculated the FI for the trial end points of rates of grade 2 or higher moist desquamation and S aureus colonization between the 2 groups.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…The Fragility Index (FI) is an epidemiological tool that can quantitatively assess this counterfactual and determine the minimum needed change in number of events for the results to become nonsignificant . We calculated the FI for the trial end points of rates of grade 2 or higher moist desquamation and S aureus colonization between the 2 groups.…”
mentioning
confidence: 90%
“…The findings from Kost et al of significantly reduced rates of moist desquamation and S aureus colonization are notable and robust. Future investigations on this topic could be encouraged to be validated in other and larger settings.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently published studies have suggested an association between nasal microbiome colonization and severity of radiodermatitis, as well as radiodermatitis recovery outcomes based on skin microbiome . Furthermore, a randomized clinical trial showed that skin decolonization may be effective for acute radiodermatitis prophylaxis . However, to our knowledge, research has yet to unravel the pathomechanism and association of the skin microbiome before and during radiotherapy with radiodermatitis severity.…”
Section: Introductionmentioning
confidence: 99%